Trade shock, refugee, and the rise of right-wing populism: Evidence from European Parliament elections - Yuchen Lin; Tianyang Xi (China Economic Quarterly International, 2022)
Recent years have witnessed the rising support for right-wing populism in European politics. We rely on the outcomes of the 2014 European Parliament elections to empirically examine the economic and cultural mechanisms that fuel this trend. Using import competition to measure economic shocks and regional-level refugee shocks, we find that regions exposed to more intense trade shocks are more likely to vote for right-wing parties. We further show the increasing support for economically far-right parties is mainly caused by trade shocks, and the electoral support for culturally far-right parties stems mainly from refugee shocks.